Forced gifts: The burden of being a friend - Bulte, Erwin; Wang, Ruixin; Zhang, Xiaobo (International Food Policy Research Institute, 2017)
In many developing countries, gift expenses account for a substantial share of total household expenditures. As incomes rise, gift expenses are escalating in several developing countries. We develop a theoretical model to demonstrate how (unequal) income growth may trigger “gift competition” and drive up the financial burden associated with gift exchange. We use unique census-type panel data from rural China to test our model predictions and demonstrate that (1) the value of gifts responds to the average gift in the community, (2) the escalation of gift giving may have adverse welfare implications (especially for the poor), and (3) escalating gift expenses crowd out expenditures on other consumption items.